Clinical effects of 2 commercially available diets on canine atopic dermatitis - Boehm, Teresa M. S. A.; Klinger, Christoph J.; Udraite-Vovk, Laura; Navarro, Christelle; Mueller, Ralf S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Canine atopic dermatitis (CAD) is a common skin disease in dogs. Prior studies were able to determine beneficial effects of essential fatty acids (EFA) on the clinical signs of CAD. The aim of this study was set to evaluate the effects of a newly designed, EFA-enriched diet on the clinical signs of CAD compared to another EFA-enriched diet.Materials and methods In this prospective, randomized, double-blinded study, 31 privately owned dogs with atopic dermatitis received either the control diet (diet A, Hill’s Prescription Diet™ d/d™ Salmon & Rice, n = 17) or the test diet (diet B, Veterinary HPM™ Dermatology Support D1, Virbac, n = 14) for 12 weeks. At the beginning of the study as well as after 4, 8 and 12 weeks, skin lesions and pruritus were evaluated via validated scores and the administered medication was documented. At the same time, the dogs’ coat quality was evaluated via a distinct scoring system. In both groups, a total of 7 dogs each completed the entire study.Results After 12 weeks, there was a mild improvement in lesion scores, pruritus and coat quality with both diets.Clinical relevance In this study, both diets improved the patients’ skin lesions pruritus and coat quality.
Keywords: Essential fatty acids; nutritional value; atopy; dog